2001
DOI: 10.1021/jp003868k
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoshells:  Variations in Morphologies and Optical Properties

Abstract: The production of silica core-silver shell nanoparticles (silver nanoshells) by three different chemical methods is described. Each method produces a silver outer layer with a unique morphology, ranging from smooth and uniform, to rough on the 2-5 nm length scale, to spiky with extremely sharp, needlelike protrusions extending outward from the surface of the nanoparticle. The nanoshells produced by each growth method were studied using transmission electron microscopy and UV-vis spectroscopy. In particular, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
372
1
12

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 486 publications
(406 citation statements)
references
References 22 publications
21
372
1
12
Order By: Relevance
“…Clearly, however, the curvature of 110-nm spheres does not result in simple polystyrene core/Ag shell structures. 19 Consistent with Mie theory, 20 spherical Ag nanoparticles in DMF exhibit a single-surface plasmon resonance centered at 415 nm. The Ag nanodisks presented here exhibit optical properties that are remarkably different from those of spherical Ag nanoparticles.…”
mentioning
confidence: 60%
“…Clearly, however, the curvature of 110-nm spheres does not result in simple polystyrene core/Ag shell structures. 19 Consistent with Mie theory, 20 spherical Ag nanoparticles in DMF exhibit a single-surface plasmon resonance centered at 415 nm. The Ag nanodisks presented here exhibit optical properties that are remarkably different from those of spherical Ag nanoparticles.…”
mentioning
confidence: 60%
“…More recently, the localized surface plasmon resonance ͑LSPR͒ nanosensor becomes a hot spot due to their unique characteristics and potential market in the life sciences. [2][3][4][5][6] The LSPR nanosensor can be implemented through extremely simple, small, light, robust, low cost equipment. It has many advantages such as convenience, high sensitivity, wide application, real-time detection, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Scientist gained significant control both the over size [7] and surfaces [8][9][10][11][12] for nanoparticles. They have demonstrated that anisotropy in nanostructure like triangular prisms [13][14][15][16][17][18], nanoscale rods [19][20][21][22][23][24][25][26], nanoshells [27][28][29][30][31], multipods [32][33][34], disks [35][36][37][38][39] and cubes [40][41][42] shows better performance over solid spheres. …”
Section: Nanomaterials and Nanotechnologymentioning
confidence: 99%